Lanterne nel buio digitale: Riconquistare l’autorità e gli archivi di dissenso di Amitav Ghosh contro la cultura degli influencer - Harjot Banga (RiCognizioni, 2025)
ABSTRACT · Lanterns in the Digital Dark: Reclaiming Authority and Amitav Ghosh’s Archives of Dissent Against Influencers Culture. This article responds to two primary objectives: first, delving into the problem of cultural authority in the digital age, second, intellectuals’ and writers’ responses to authority crisis as they embrace and make their way through the digital environment. Thus, the article juxtaposes the emergence of conformist influencers—new “priests” of superficial materialism—with writers’ enduring function as critical intellectuals. Based on the scholarship of thinkers such as Edward Said, Michel Foucault, and Jacques Derrida, this thesis argues that even as social media incentivizes virality and instant consumption, thoughtful authors are consciously occupying digital space to construct richer and more nuanced discourse. Using as case study Amitav Ghosh’s online presence, this article demonstrates how committed and engaged writers today can build rich, interactive archives that wed intellectual depth to digital reach. Ghosh’s website, examined through the lens of Derrida’s conception of the archive as an expression of a specific type of power, is more than a holding cell of information, rather it is also a place of continued cultural conversation and active engagement, a counterpoint to the emptiness of influencer culture.